Classification of TV Programs According to Their Topics Using the XLNet Model - Vo, Quang Long; Nguyen, Ngọc Hùng Anh; Tran, Minh Sơn; Tran, Thu Hà (Journal of Technical Education Science, 2022)
While observing the behavior of TV viewer, the HCMUTE researchers concluded that TV spectators rather watch the content of the TV channel than the channels themselves. The latters are just the containers / carriers of the precious TV information inside. Therefore to enable TV viewers to access directly the content, a new TV user graphic interface is offered to them: the TV program list is ordered by the topics of the broadcasted programs but not the channels carrying them. Therefore, viewers can now choose a program according to topics of interest, not via a intermediate step by selecting channel with dummy name / number. To classify all the broadcast programs, the researchers propose a sequence-to-sequence Model to organize these programs into one of five predefined topics / themes: feature films, news, music, sports and synthesis. The XLNet network is incorporated in the classification. TV channels currently playing the program with the selected theme will be displayed so that viewers can quickly access the wish content.